Assessing the Ability of Hospital Diagnosis Codes to Detect Inpatient Exposure to Antibacterial Agents. (20th February 2018) - Ray, Michael J.; Trick, William E.; Lin, Michael Y.
Abstract : OBJECTIVE: Because antibacterial history is difficult to obtain, especially when the exposure occurred at an outside hospital, we assessed whether infection-related diagnostic billing codes, which are more readily available through hospital discharge databases, could infer prior antibacterial receipt. DESIGN: Retrospective cohort study. PARTICIPANTS: This study included 121, 916 hospitalizations representing 78, 094 patients across the 3 hospitals. METHODS: We obtained hospital inpatient data from 3 Chicago-area hospitals. Encounters were categorized as "infection" if at least 1 International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) code indicated a bacterial infection. From medication administration records, we categorized antibacterial agents and calculated total therapy days using Centers for Disease Control and Prevention (CDC) definitions. We evaluated bivariate associations between infection encounters and 3 categories of antibacterial exposure: any, broad spectrum, or surgical prophylaxis. We constructed multivariable models to evaluate adjusted risk ratios for antibacterial receipt. RESULTS: Of the 121, 916 inpatient encounters (78, 094 patients) across the 3 hospitals, 24% had an associated infection code, 47% received an antibacterial, and 13% received a broad-spectrum antibacterial. Infection-related ICD-9-CM codes were associated with a 2-fold increase in antibacterial administration compared to those lacking such codes (RR, 2.29; 95% confidence interval [CI], 2.27–2.31) and a 5-fold increased risk for broad-spectrum antibacterial administration (RR, 5.52; 95% CI, 5.37–5.67). Encounters with infection codes had 3 times the number of antibacterial days. CONCLUSIONS: Infection diagnostic billing codes are strong surrogate markers for prior antibacterial exposure, especially to broad-spectrum antibacterial agents; such an association can be used to enhance early identification of patients at risk of multidrug-resistant organism (MDRO) carriage at the time of admission. Infect Control Hosp Epidemiol 2018;39:377–382